2020
DOI: 10.1021/acsomega.0c05256
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Capability of Lactobacillus plantarum W1 Isolated from Soybean Whey in Producing an Exopolysaccharide

Abstract: This study aims at producing exopolysaccharides (EPS) from a lactic acid bacterial strain. The soybean whey-isolated Lactobacillus plantarum W1 (EPS-W1), which belongs to genus Lactobacillus, is identified using the phenylalanyl-tRNA sequencing method. Of all the examined strains, R-49778 (as numbered by BCCM/LMG Bacteria Collection, Ghent University, Belgium) showed the highest capability of producing exopolysaccharides. Structural characterization revealed a novel exopolysaccharide consisting of repeating un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Moreover, the presence of multiple signal peaks at δ 4.5-5.5 ppm implied that the isolated EPS was a heteropolysaccharide consisting of multiple monosaccharides. The EPS produced by L. plantarum W1 had six ectopic proton signals (δ 5.76, 5.67, 5.59, 5.59, 5.56, 5.55, 5.37 ppm) in the anomalous region (δ 4.5-5.5 ppm), showing that the EPS samples were composed of seven monosaccharides of heteropolysaccharides (Do et al, 2020), which was different from the results of this test. Therefore, the isolated EPS was inferred to be a pyranose consisting of α-(1 → 6) and α-(1 → 3) glycosidic bonds.…”
Section: Nuclear Magnetic Resonance Spectroscopy Analysiscontrasting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the presence of multiple signal peaks at δ 4.5-5.5 ppm implied that the isolated EPS was a heteropolysaccharide consisting of multiple monosaccharides. The EPS produced by L. plantarum W1 had six ectopic proton signals (δ 5.76, 5.67, 5.59, 5.59, 5.56, 5.55, 5.37 ppm) in the anomalous region (δ 4.5-5.5 ppm), showing that the EPS samples were composed of seven monosaccharides of heteropolysaccharides (Do et al, 2020), which was different from the results of this test. Therefore, the isolated EPS was inferred to be a pyranose consisting of α-(1 → 6) and α-(1 → 3) glycosidic bonds.…”
Section: Nuclear Magnetic Resonance Spectroscopy Analysiscontrasting
confidence: 85%
“…In addition, EPSs produced by some LAB are heteropolysaccharides composed of different monosaccharide structures. Do et al (2020) found that EPS-W1 produced by L. plantarum was a heteropolysaccharide composed of glucose and mannose. The SSC-12 EPS produced by Pseudomonas pentosus was a heteropolysaccharide composed of glucose, mannose, galactose, arabinose, and rhamnose ( Fan et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It turns out that Fraction I, which contained the highest amount of neutral carbohydrates (96%), was concentrated, lyophilized, and purified on a Sephadex G-100 column (10 mm × 600 mm) before being eluted with deionized water, NaCl 0.1 M, and NaCl 0.3 M eluents (flow rate, 0.2 mL/min), respectively. Finally, the achieved PS was obtained for further investigations. , …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the achieved PS was obtained for further investigations. 30,31 2.4. Determination of Molecular Mass.…”
Section: Extraction Of Psmentioning
confidence: 99%
“…Soybean whey, as a byproduct produced of L. plantarum W1 named EPS-W1 marked by phenylalanyl-tRNA sequencing method using a set of primers for PCR amplification, shows remarkable properties in production aspects, such as in functional foods, food industries, and biomedical applications [119]. Some other LAB spp.…”
Section: Lactobacillus Eps As An Immunomodulatory Agentmentioning
confidence: 99%